Factors determining the growth of SMEs: Evidence from registered SMEs in Northern Province, Sri Lanka - Kengatharan, L. (International Journal of Accounting & Business Finance Vol.6.No.2 December 2020 Issue. pp. 19 - 31, 2020)
The objectives of this study were to explore the factors determining the growth of SMEs in the Northern Province of Sri Lanka and to examine the influence of those factors on the growth of SMEs. A field survey was conducted to collect the necessary data from the owners/ managers of 189 SMEs which are functioning in the Northern Province of Sri Lanka. Self reported questionnaire was designed to recognize the factors that influence the growth of SMEs. Data were analysed with SPSS 22 and SmartPLS. Exploratory Factor Analysis was performed to identify the factors influencing growth of SMEs. As a result, need for achievement, motivation, location, business environment, accounting and control and network were recognized as factors influencing on the growth of SMEs. PLS - SEM was performed to assess the impact of these factors on the growth of SMEs. The results of the study revealed that need for achievement and business environment had a medium size influence on growth. The rest of the factors had the small effect on growth. Overall, this study has made parametric contributions as identified the factors influencing the growth of SMEs and geographical contribution as investigated the effect of indentified factors on the growth of SMEs of Northern Province in Sri Lanka
Keywords: Business Environment; Growth; Need for Achievement; SMEs; Northern Province